Educational level and memory/metamemory in different age and sex groups - Zarevski, Predrag (Array, 1996)
On a representative sample of 240 subjects divided into six age groups of 40 subjects each, half male/female, following aspects of memory were assessed: short term memory, working memory, and episodic memory as well as the aspects of metamemory including evaluation of different dimensions of own memory functioning and frequency of the use of external memory aids. Differences in averages and relations of measured constructs with educational level in various subsamples of subjects are discussed.